Comparative Evaluation of Clinical and Microbiological Assessment of Caries Excavation Using Conventional, Smart Bur, Chemomechanical Method and ErCr:YSGG Laser - Annapoorna Kini; Prerana Kothari; R. Sujith; Nithin Shetty; Blesy K. Varughese; Sheetal C. Kasargod (Wolters Kluwer Medknow Publications, 2024)
Objectives: Caries removal efficacy in terms of microbiological burden using Tungsten Carbide Bur No. 330, Polymer bur, BRIX 3000, and ErCr:YSGG Laser. Methods: Class I open dentinal caries was selected and divided into four groups (n = 15) depending on caries excavation methods. Group I: Tungsten carbide (TC) No 330-bur; Group II: Polymer bur (Smart bur); Group III: Brix 3000 gel; Group IV: Erbium, chromium-doped yttrium, scandium, gallium, and garnet (Er:Cr:YSGG) laser. Two samples of carious material, before and after caries excavation, were taken and cultured on blood agar plates. Multiple comparison of mean CFUs/ml between different groups was done using Dunn's post hoc test and Wilcoxon signed-rank test. Results: Group I showed significantly lesser mean CFUs/ml followed by Group IV as compared to Group II and Group III. Conclusion: Within the parameters and limitations of the present study, ErCr:YSGG laser can be a helpful aid as a minimally invasive method of caries excavation.